Cystoidosoma hermaphroditus sp. n., the first representative of the quill mite family Ascouracaridae (Acari: Astigmata: Pterolichoidea) from an owl (Aves: Strigiformes) - Hernandes, Fabio Akashi [UNESP] (2015)
The mite family Ascouracaridae Gaud et Atyeo, 1976 contains large-sized mites (mostly > 1 mm) which live inside the quills of birds of several orders. To date, no representative of this family has been found associated with the order Strigiformes (owls). In this paper, a new species of this family, Cystoidosoma hermaphroditus sp. n., is described from the tropical screech owl, Megascops choliba (Vieillot) (Aves: Strigiformes) from Brazil. This species is unique in having an external spermaduct, a primary duct and a rudimentary bursa copulatrix present in males. This is the first astigmatan feather mite described from the order Strigiformes in this country. A key to adults of the genus Cystoidosoma Gaud et Atyeo, 1976 of the world is presented.